Analisis Beban Kerja Karyawan Departemen Perakitan PT XYZ Dengan Menggunakan Metode Full Time Equivalent - Noval Cahyo Triyanto; Sonny Taufan; Dadi Mahardi; Kasduni; Mustofa; Imam Haryono; Iskandar, Donant Alananto (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2024)
PT XYZ has not evaluated the workload received by employees in the fan grille part in the assembly department and the management of PT XYZ does not yet know the effectiveness of the work of employees in the fan grille part in the assembly department after carrying out labor efficiency. From the results of workload calculations using the FTE method after labor efficiency, there is 1 operator who has ineffective work effectiveness because the operator's FTE value is overloaded (> 1.28), including operator 1 with an FTE value of 1.36 while 5 other operators have effective work effectiveness because the FTE value of the five operators is <1.28, including operator 2 has an FTE value of 1.17, operator 3 has an FTE value of 1.11, operator 4 has an FTE value of 1.23, operator 5 has an FTE value of 1.18 and operator 6 has an FTE value of 1.22.